A microporous Cu-MOF with optimized open metal sites and pore spaces for high gas storage and active chemical fixation of CO2. Issue 74 (23rd August 2016) - Gao, Chao-Ying; Tian, Hong-Rui; Ai, Jing; Li, Lei-Jiao; Dang, Song; Lan, Ya-Qian; Sun, Zhong-Ming
Abstract : A novel Cu-MOF featuring optimized open metal sites and pore spaces displays excellent performance in terms of gas storage and heterogeneous catalysis activity. Abstract : A microporous Cu-MOF with optimized open metal sites and pore space was constructed based on a designed bent ligand; it exhibits high-capacity multiple gas storage under atmospheric pressure and efficient catalytic activity for chemical fixation of CO2 under mild conditions.